THE EFFECT OF NATURAL GUANO ORGANIC FERTILIZER ON GROWTH AND YIELD OF SPRING ONION (ALLIUM FISTULOSUM L.) - Musadia Afa (Agrotech Journal, 2016)
A field experiment was aimed at investigating the effect of natural guano organic fertilizers on growth and yield of Spring Onion (Allium fistulosum L.). The experiment was conducted from September to Nopember, 2014 in Unamendaa Village, Kolaka District. It was prepared by using a randomized block design  (RBD) with single factor namely doses of natural guano organic fertilizers. The treatments consisted of 4 levels were : (1) G0 = control or no treatment, (2) G1 = dose of 6 kg unit-1 (equivalent to 5 t. ha-1), (3) G2 = dose of 12 kg unit-1 (equivalent to 10 t. ha-1) and (4) G3 = dose of 18 kg unit-1 (equivalent to 15 t. ha-1), respectively. Every treatment was replicated 3 times, therefore overall there were 12 experimental units. Data was collected on growth and yield parameters of Spring Onion : (1) plant height, (2) number of leaves, (3) number of tillers, (4) diameters of stem and (5) yield (plant fresh weight unit-1). Data obtained were analyzed using Analysis of Variance (Anova) and followed by Duncan’s Multiple Range Test (DMRT) at the 1 % level. The result of experiments showed that fertilizations using natural guano organic was significantly affected on : plant height, number of leaves, number of tillers, diameter of stem and plant fresh weight, respectively. Untill fertilization of 18 kg unit-1 (G3) were able to increased the growth and yield of Spring Onion, hence it was showed better performance on all parameters